2011
DOI: 10.2139/ssrn.1957697
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Factors of Emerging Stock Market: The Evidence from Thailand

Abstract: This paper aims to examine the importance of macroeconomic factors to determine the performance of stock market. The regression analysis is used to examine this relationship. The result shows that macroeconomic variables can explain stock return significantly after adjusting for some lags of data availability. Moreover, the lead-lag relationship is examined by Vector Autoregression model and Granger causality test. They reveal that macroeconomic variables are less important to predict future stock return where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
5
0
4
Order By: Relevance
“…This result is also similar to studies of Singh,T. et al(2011), and Tangjitprom (2011) done on Taiwan, Turkey and Thailand respectively stating that unemployment doesn't have any significant influence on stock returns. Our study finds a unidirectional causality between the variables.…”
Section: Turkish Studiessupporting
confidence: 91%
See 3 more Smart Citations
“…This result is also similar to studies of Singh,T. et al(2011), and Tangjitprom (2011) done on Taiwan, Turkey and Thailand respectively stating that unemployment doesn't have any significant influence on stock returns. Our study finds a unidirectional causality between the variables.…”
Section: Turkish Studiessupporting
confidence: 91%
“…(2016) discloses the presence of long run relation between the BSE Sensex and select macroeconomic indicators viz., Exchange Rate, wholesale price index, T-bill rates and M3 in their study in India. Pal & Mittal (2011) & Gunasekarage et al (2004 also showed a significant relationship between macroeconomic variables and stock returns, but a different outcome has been observed in the study of Tangjitprom (2011) who found insignificant relationship between Interest rate, exchange rate and stock returns in his study on Thailand. Tangjitprom (2011) cited unemployment rate as a factor that represents general business condition and business cycle of a country.…”
Section: Literature Reviewmentioning
confidence: 70%
See 2 more Smart Citations
“…Empirical studies showed that the performance of stock exchange in emerging market is the good leading indicator for future macroeconomic conditions. Tangjitprom [23] proved this phenomenon in his study. Mahmood and Dinniah [24] studied this relationship for six Asia pacific countries and found that there is short term relationship between economic factors and capital markets.…”
Section: Literature Reviewmentioning
confidence: 83%